2015
DOI: 10.29173/cmplct23817
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Teacher Education Thinking: Complexity and Relational Ways of Knowing

Abstract: In order that teacher education programs can act as significant scaffolds in supporting new teachers to become informed, creative and innovative members of a highly complex and valuable profession, we need to re-imagine ways in which teacher education programs operate. We need to re-imagine how courses are conceptualized and connected, how learning is shared and how knowledge, not just “professional”, but embedded knowledge in authentic contexts of teaching and learning is understood, shaped and re-applied. Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 28 publications
0
27
0
2
Order By: Relevance
“…More specifically, and in common with an increasing number of authors, (e.g. Opfer and Pedder 2011, Cochran-Smith et al 2014, Sanford, et al 2015, we seek to contribute to this professional learning debate by exploring how ideas from complexity thinking and ecological perspectives have the potential to act as a conceptual lens to help us better understand, design and support teachers' long term professional learning.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, and in common with an increasing number of authors, (e.g. Opfer and Pedder 2011, Cochran-Smith et al 2014, Sanford, et al 2015, we seek to contribute to this professional learning debate by exploring how ideas from complexity thinking and ecological perspectives have the potential to act as a conceptual lens to help us better understand, design and support teachers' long term professional learning.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, one or two courses each term in the program were still focused on covering content and using tests to ensure TCs read course material; however, the contrasting experience in the TRUVIC cluster of courses meant that TCs came to appreciate the collective self-organizing, adaptive, and emergent form of learning that was being modelled. As was noted in Sanford et al (2015), the TRUVIC students formed a collective consciousness that observed, became comfortable in a school (in different pedagogical spaces), got to know adolescent students, then volunteered to teach as they saw how they could contribute to the school teachers' lessons. This process shifted how students as a cohort and their instructors as a collective described the world of teaching, as they learned to teach with a relational epistemology, interact with adolescents and bring forth the knowledge of being a teacher from different pedagogical spaces.…”
Section: Resultsmentioning
confidence: 85%
“…In agreement, we have explored this application of complexivist philosophy. Emphasizing the interaction of parts in a TE program and working from the ground up, we have focused on a relational approach to knowing that offers a perspective that frames human learning and the cognitive processes it entails as distributed in the world and our interactions in that world (Sanford, Hopper & Starr, 2015).…”
Section: Trouver Une Trame Connective En Formation Des Maitres : Créamentioning
confidence: 99%
See 2 more Smart Citations